Elżbieta Drygas – poznańska pedagożka, „teatralniczka” i działaczka społeczna – refleksja u progu 50-lecia pedagogiki „łejerskiej” - Sadowska , Katarzyna (Studia Edukacyjne, 2024)
This study aims to present the teaching achievements of Elżbieta Drygas – a Poznań teacher, theatre instructor, social activist, and winner of the Order of the Smile and the Irena Sendler Award for repairing the world, co-founder of Emilia Waśniowska Primary School No. 83 in Poznań. The reflection applied the biographical method using the technique of analyzing existing and retrieved sources, including the few available studies that allow obtaining knowledge about “Łejery” pedagogy, articles from periodical publications, electronic sources related to “Łejery” pedagogy, graduation and doctoral theses prepared at Polish universities, press releases, and free conversations and interviews conducted with Elżbieta Drygas and Jerzy Hamerski by the author of the study in the school year 2023/2024 at the “Łejery” school. The current state of research on the phenomenon of “Łejery” pedagogy and the profiles of the founders of the unique school with theatre in Poland is insufficient. Therefore, on the cusp of the 50th jubilee of “Łejery” pedagogy, it seems justified to undertake considerations in this area on many levels, presenting the profile, experiences, motivation, and achievements of the co-founder of this institution, without whom “Łejery” pedagogy would not have its unique systemic solutions.